After the Storm Post-Pandemic Trends in the Southern Mediterranean - Kortunov, Andrey (ISPI Publications, 2020)
The Mediterranean region has faced a significant number of challenges that have stemmed from turbulent events taking place on its Southern shores: conflicts and instability, the migration crisis, disruptions of regional value chains, souring regional relations, and foreign power interferences that have severely affected the region. The Covid-19 pandemic wreaked havoc on the Southern Mediterranean, but the health crisis had ambiguous effects on the underlying economic, social, and political trends of the region. It has exposed and exacerbated much of the previous sources of tension and, obscured many of them as public attention moved towards facing the public health emergency. Will the Covid-19 pandemic spur governments and civil societies to action? Or will it just serve as another smokescreen behind which to hide the region's longstanding problems?